Relationship Between Physical Activity and Blood Pressure in Hypertensive Elderly at UPTD Puskesmas Susut I - Wulandari, Ni Putu Dita; Sukmandari, Ni Made Ari; Riantini, Ni Ketut Ari (Fakultas Kedokteran, 2023)
Introduction: Hypertension is a common problem experienced by some elderly due to several changes in the body's system. This condition is also influenced by several other factors such as decreased activity ability in old age. This study aimed to determine the relationship between physical activity and blood pressure in hypertensives elderly at the Working Area of UPTD Puskesmas Susut I. Method: This study used a correlational analytic design with a cross sectional approach. This study involved 83 samples selected through purposive sampling technique. Data were collected using the Physical Activity Scale for Elderly (PASE) questionnaire and analyzed using the Rank Spearman test. Result: The results showed that the physical activity of the elderly had an average value of 11.43 or categorized as mild physical activity with an average systolic blood pressure was 157 mmHg and diastolic blood pressure was 97 mmHg. There is a relationship between physical activity and blood pressure in hypertensives elderly at the working area of UPTD Puskesmas Susut I (p-value = 0.000). Conclusion: There is a relationship between physical activity and blood pressure in hypertensives elderly. This research can improve nursing services for the elderly with hypertension through providing activities that can increase the physical activity of the elderly